Imbalanced Host Response to SARS-CoV-2 Drives Development of COVID-19 - Blanco-Melo, Daniel; Nilsson-Payant, Benjamin E.; Liu, Wen-Chun; Uhl, Skyler; Hoagland, Daisy; Møller, Rasmus; Jordan, Tristan X.; Oishi, Kohei; Panis, Maryline; Sachs, David; Wang, Taia T.; Schwartz, Robert E.; et al. (Cell, 2020)
Viral pandemics, such as the one caused by SARS-CoV-2, pose an imminent threat to humanity. Because of its recent emergence, there is a paucity of information regarding viral behavior and host response following SARS-CoV-2 infection. Here we offer an in-depth analysis of the transcriptional response to SARS-CoV-2 compared with other respiratory viruses. Cell and animal models of SARS-CoV-2 infection, in addition to transcriptional and serum profiling of COVID-19 patients, consistently revealed a unique and inappropriate inflammatory response. This response is defined by low levels of type I and III interferons juxtaposed to elevated chemokines and high expression of IL-6. We propose that reduced innate antiviral defenses coupled with exuberant inflammatory cytokine production are the defining and driving features of COVID-19. [Display omitted] •SARS-CoV-2 infection induces low IFN-I and -III levels with a moderate ISG response•Strong chemokine expression is consistent across in vitro, ex vivo, and in vivo models•Low innate antiviral defenses and high pro-inflammatory cues contribute to COVID-19 In comparison to other respiratory viruses, SARS-CoV-2 infection drives a lower antiviral transcriptional response that is marked by low IFN-I and IFN-III levels and elevated chemokine expression, which could explain the pro-inflammatory disease state associated with COVID-19.